Risk Factors of Unfavorable Outcomes, Major Bleeding, and All-Cause Mortality in Patients with Venous Thromboembolism - Han Young Lee; Tae Hoon Yeo; Tae Kyung Heo; Young Gyu Cho; Dong Hui Cho; Kyung Bok Lee (Vascular Specialist International, 2021)
Purpose: This study aimed to analyze the clinical outcomes of venous thromboembolism (VTE) patients and identify the risk factors for VTE-related unfavorable outcomes, major bleeding, and 30-day all-cause mortality. Materials and Methods : From January 2016 to December 2020, 198 patients with confirmed VTE were enrolled. Potential risk factors for unfavorable outcomes, major bleeding, and all-cause mortality were analyzed. Results : VTE-related unfavorable outcomes developed in 13.1%, while 30-day all-cause mortality was 8.6%. In the multivariate analysis, a pulse ≥110/min and respiratory rate ≥30/min were statistically significant predictors for VTE-related unfavorable outcomes. Diabetes was a significant risk factor for major bleeding. In addition, a history of malignancy, no anticoagulation treatment, and need for mechanical ventilation were significant predictors of all-cause mortality. Conclusion : VTE-related mortality and morbidity rates remained high. In cases of tachycardia and tachypnea, early aggressive treatment is needed to prevent unfavorable outcomes. Patients with risk factors should be closely monitored.